High-voltage-resistant brominated flame-retardant polyamide composition and preparation method thereof
By optimizing the composition and processing technology of brominated flame-retardant polyamide compositions, their flame retardancy and tracking resistance under high voltage are improved, solving the problem of poor tracking resistance of brominated flame-retardant polyamides under high voltage in the prior art, and achieving safety and cost-effectiveness in high voltage environments.
Patent Information
- Application Number
- CN202511853475.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-10
- Publication Date
- 2026-01-27
AI Technical Summary
Existing brominated flame-retardant polyamides have poor tracking resistance under high voltage, making it difficult to meet the high-voltage application requirements of new energy vehicles and photovoltaic products. Furthermore, existing improvement methods suffer from reduced mechanical properties or increased costs.
Flame-retardant polyamide compositions are prepared by melt blending aliphatic polyamide, anionic brominated polystyrene, antimony pentoxide, zinc aromatic carboxylate, and hydroxyapatite using a single-screw or twin-screw extruder. The component ratios and processing techniques are optimized to improve flame retardancy and electrical tracking resistance.
It achieves a relative tracking index (CTI) greater than 400V and an inclination tracking index (IPT) greater than 1kV, while also possessing high flame retardancy and cost-effectiveness, making it suitable for high-voltage environments.
Smart Images

Figure SMS_1 
Figure SMS_5 
Figure SMS_7
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flame retardant materials technology, specifically relating to a high-voltage resistant brominated flame retardant polyamide composition and its preparation method. Background Technology
[0002] As one of the ideal materials for lightweight and efficient structural design, polyamide composites possess advantages such as high specific strength, corrosion resistance, fatigue resistance, good dimensional stability, and strong design flexibility, and have long been widely used in the fields of new energy electric vehicle (EV) and photovoltaic (PV) connectors. According to the power formula P=U×I, when the voltage (U) is increased, the current (I) will decrease inversely, while the line loss (P) will decrease. 损耗 P is proportional to the square of the current (I): 损耗 =I²R, a decrease in current leads to a quadratic decrease in losses. Therefore, both new energy vehicles and the photovoltaic field are accelerating towards higher voltage and larger electrical load technology platforms in order to improve the efficiency of energy conversion and transmission. For example, new energy vehicle battery technology has already widely adopted 400V voltage and is evolving towards 800V voltage. In the future, electric vehicles are expected to achieve shorter charging times, longer driving ranges, and more efficient energy management.
[0003] However, compared to low-voltage operating conditions, components using polymer materials face a higher risk of short circuits under high-voltage conditions. Tracking is a major cause of insulation failure in polymer materials under humid conditions. When moisture, dust, or other contaminants adhere to the surface of polymer components during use, repeated micro-discharges can create conductive pathways on the surface, leading to dielectric breakdown (tracking) and sometimes short circuits between electrodes. Furthermore, carbonization of polymer materials under high-temperature electric arcs is also a significant factor contributing to tracking, which in turn induces creepage, breakdown, and fire.
[0004] In the industry, the relative tracking index (CTI) of materials is mainly used to evaluate the resistance of thermoplastics to tracking under the combined effect of electric field and electrolyte. CTI is a test method to evaluate the accelerated tracking of insulating materials under humid and contaminated conditions. It involves applying a voltage between two electrodes placed on the material surface and applying 50 or 100 drops of contaminating liquid (0.1% ammonium chloride aqueous solution), thereby accelerating the aging process to form carbide conductive channels (tracks) to assess the material's ability to resist the chain reaction of "leakage → arcing → carbonization → conductivity". The CTI value is defined as the highest voltage value at which no tracking (conductive channel) is formed and no burning / breakdown occurs.
[0005] Brominated flame-retardant polyamide composites exhibit higher flame-retardant efficiency than halogen-free materials. Brominated flame retardants function at specific stages of the combustion process in thermoplastic compositions, such as during ignition or flame spread. At high temperatures, the carbon-bromine bonds in the flame retardant break, releasing bromine free radicals that effectively capture free radicals generated by the thermal degradation of the polymer material. This effectively reduces the concentration of free radicals, thereby mitigating or terminating the free radical chain reaction of combustion. Furthermore, the hydrogen bromide released from the decomposition of brominated flame retardants is non-flammable, effectively blocking oxygen and inhibiting the combustion reaction.
[0006] However, brominated flame retardant technology, which has been widely used in the industry for many years, is facing challenges brought by the high-voltage era. Firstly, brominated flame retardant technology uses antimony trioxide and bromine flame retardants for synergistic flame retardancy. Antimony trioxide is an essential component, but it degrades the material's resistance to electro-tracking. Secondly, bromine flame retardants have low carbon-bromine bond energies, especially aliphatic chain carbon-bromine bonds, which break at around 200°C, releasing hydrogen bromide. Hydrogen bromide reacts with water to produce bromine acid, corroding and carbonizing the material surface, further degrading the material's resistance to electro-tracking. These factors result in brominated flame-retardant polyamides typically achieving a CTI value of only 250V to 350V, especially for black products where the CTI value is usually below 300V. This makes it difficult for brominated flame-retardant polyamides to meet the high-voltage application trends of new energy vehicles and photovoltaic products.
[0007] Therefore, improving the voltage resistance of brominated flame-retardant polyamide compositions to ensure stable insulation even under long-term high temperature and humidity conditions is crucial for safety in high-voltage applications. In existing technologies, the CTI value of brominated flame-retardant polyamides is improved by developing other electrically friendly flame retardants to replace antimony trioxide and bromine flame retardants. For example, patent document CN104693792A completely replaces antimony trioxide with phosphogypsum powder, improving the CTI value by approximately 100V compared to the antimony trioxide-based method. However, phosphogypsum's high hygroscopicity significantly negatively impacts the mechanical properties of the composite material, limiting its application. Patent document CN112759927A partially replaces antimony trioxide and bromine flame retardants with zinc borate and melamine-based flame retardants, preparing flame-retardant polyamide materials that pass the CTI 350V test. However, zinc borate and melamine-based flame retardants have poor temperature resistance, and the resulting compositions are prone to generating gas during injection molding. Another common technical approach is to add tracking modifiers to thermoplastic compositions. For example, patent document CN113574104A improves the CTI value of easily hydrolyzed polymers (such as PET and PBT) and polyamides containing polar groups by adding carbodiimide compounds, but this technical solution has a relatively limited effect on improving the compressive strength of the material. Patent document CN114196199A uses hydrotalcite to neutralize free bromine in the composition, thereby improving the polymer's anti-tracking properties. However, hydrotalcite can easily affect flame retardant stability because hydrogen bromide plays an important role in the polymer's flame retardant process. If hydrogen bromide is excessively neutralized by acid scavengers during combustion, it will lead to unstable flame retardant properties of the composition.
[0008] In addition, some technical workers have provided solutions to improve electrical performance from the perspective of polymer structure. For example, patent document CN115989272A proposes that by using long-chain aliphatic polyamides with an average of 6 carbon atoms (excluding carbon atoms in the carbonyl group) per amide group, the tracking performance on inclined surfaces at voltages above 1kV can be improved. Patent document CN115516006A proposes that by combining alicyclic diamine bis(aminoalkyl)cyclohexane or the alicyclic dicarboxylic acid cyclohexanedicarboxylic acid into polyamide, the relative tracking index (CTI) retention rate is significantly improved after thermal aging. However, compared with the use of general-purpose aliphatic polyamides (such as PA6, PA66), the cost of such materials is significantly increased, thus affecting the product's competitiveness in the market.
[0009] In summary, existing technologies address the poor tracking resistance of brominated flame-retardant polyamides by primarily employing the following methods: replacing general-purpose polyamides with long-chain aliphatic or semi-aromatic polyamides; replacing antimony trioxide and brominated flame retardants with mineral, zinc borate, and nitrogen-based flame retardants; or using hydrolysis inhibitors and acid scavengers to mitigate polymer surface hydrolysis and carbonization, thereby improving tracking resistance. However, these methods still have shortcomings. Current technologies have not yet proposed a brominated flame-retardant polyamide composition that combines excellent electrical properties under high voltage with high-level flame retardancy and cost competitiveness. Summary of the Invention
[0010] In view of the above-mentioned shortcomings of the prior art, the main objective of the present invention is to provide a high-voltage resistant brominated flame-retardant polyamide composition, specifically a brominated flame-retardant polyamide composition with a relative tracking index (CTI) greater than 400V and which combines high flame retardancy with cost-effectiveness.
[0011] Another object of the present invention is to provide a method for preparing the high-voltage resistant brominated flame-retardant polyamide composition, which is simple in process and easy to industrialize.
[0012] To achieve the above objectives, the present invention adopts the following technical solution:
[0013] In a first aspect, the present invention provides a high-voltage resistant brominated flame-retardant polyamide composition comprising the following components in weight percentage:
[0014] (A) Aliphatic polyamide 30~80 wt%
[0015] (B) Bromine-based flame retardant 10~30 wt%
[0016] (C) Antimony-based synergist 0.5~10 wt%;
[0017] (D) Aromatic carboxylic acid zinc 0.5~10 wt%
[0018] (E) Hydroxyapatite 0.5~5 wt%
[0019] (F) Reinforcing agent 0.1~50 wt%;
[0020] (G) Other adjuvants 0~5 wt%;
[0021] The sum of the mass percentages of components (A) to (G) is 100 wt%.
[0022] Component (A) is an aliphatic polyamide, which is a semi-crystalline polymer with a melting temperature of 150°C to 300°C. The melting temperature was characterized by differential scanning calorimetry (DSC) with a heating and cooling rate of 10°C / min.
[0023] In some embodiments, the aliphatic polyamide is selected from one or more of the following: PA-XY (X = number of carbon atoms in the diamine, Y = number of carbon atoms in the dicarboxylic acid) obtained by polycondensation of aliphatic dicarboxylic acid and aliphatic diamine having not less than four carbon atoms, and PA-Z (Z = number of carbon atoms in the lactam, i.e., number of carbon atoms in the repeating unit) obtained by ring-opening polymerization of lactam.
[0024] In some embodiments, the aliphatic dicarboxylic acid is selected from the group consisting of: oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, octadecanoic acid, and eicosanoic acid.
[0025] In some embodiments, the aliphatic diamine having at least four carbon atoms is selected from the group consisting of: butanediamine, pentapentanediamine, ethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecadecanediamine, octadecanediamine, nonadecadecanediamine, eicosanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine.
[0026] In some embodiments, the lactam is selected from the group consisting of α-pyrrolidone (butyrolactam), ε-caprolactam, heptanolactam, undecanolactam, and dodecanolactam.
[0027] In some embodiments, the aliphatic polyamide and monomer are selected from the following table:
[0028]
[0029] In some embodiments, the aliphatic polyamide is PA66 and / or PA6.
[0030] In some embodiments, the structure of the PA-XY type polyamide is shown in Formula I:
[0031] (I)
[0032] In formula (I), A1 represents a proton (H+) or an acetyl group (CH3-CO-); B1 represents a hydroxyl group (-OH).
[0033] The structure of the PA-Z type polyamide is shown in Formula II:
[0034] (II)
[0035] In formula (II), A1 represents a proton (H+) or an acetyl group (CH3-CO-); B1 represents a hydroxyl group (-OH).
[0036] In some embodiments, the molecular chains of the PA-XY type polyamide and the PA-Z type polyamide both contain 10~60mEq / kg terminal amino groups, preferably 10~45mEq / kg terminal amino groups, more preferably 10~30mEq / kg terminal amino groups, and the content of terminal amino groups is controlled by chemically reacting acetic acid with the terminal amino groups of the molecular chains.
[0037] The acetyl group (CH3-CO-) is formed by the chemical reaction of acetic acid (CH3-COOH) and the terminal amino group (-NH2) of the polyamide molecular chain. When A1 represents the acetyl group (CH3-CO-), it means that the terminal amino group of this part is replaced by the terminal carboxyl group for capping.
[0038] In polyamides, the electronegativity and conjugation effect of the oxygen atom in the terminal carboxyl group inhibit reactivity, while the lone pair electrons of the nitrogen atom in the terminal amine group can freely participate in the reaction. This results in the nitrogen atom adjacent to the terminal amine group being much more reactive than the terminal carboxyl group. The reactive terminal amine group degrades the flame retardant properties of polyamide materials, necessitating the addition of a higher proportion of flame retardant to achieve flame suppression. However, an excessively high proportion of flame retardant is detrimental to the composition's tracking resistance. During the polyamide polymerization stage, adding acidic substances allows the terminal amine groups to react and be eliminated during polymerization, thereby reducing the content of terminal amine groups in the polymer and improving the composition's flame retardancy and tracking resistance.
[0039] Component (B) is a brominated flame retardant aromatic bromine-containing compound selected from one of decabromodiphenyl ethane, brominated epoxy resin and brominated polystyrene, preferably brominated polystyrene.
[0040] The structure of the brominated polystyrene is shown in Formula III:
[0041] (III)
[0042] The polystyrene used as the raw material for bromination is divided into free radical polystyrene and anionic polystyrene. The weight-average molecular weight (Mw) of free radical polystyrene is 250,000~450,000, while that of anionic polystyrene is 2,000~20,000. Free radical polystyrene has a high weight-average molecular weight, resulting in poor flow properties of the flame retardant after bromination. Furthermore, styrene produced by free radical polymerization retains approximately 1% unsaturated double bonds at the ends of its molecular chains. During bromination, these unsaturated double bonds readily form aliphatic substituents with the brominating agent. The carbon-bromine bonds in aliphatic chains have relatively low bond energies, and they break at around 200°C, releasing hydrogen bromide, resulting in poor heat resistance. Therefore, anionic brominated polystyrene is preferred for preparing the brominated polystyrene used in this invention.
[0043] Component (C) is an antimony-based synergist selected from one or more of antimony trioxide, antimony pentoxide, and sodium metaantimonate, preferably sodium metaantimonate and antimony pentoxide, and more preferably antimony pentoxide.
[0044] Reactivity comparison: Antimony trioxide is a trivalent antimony oxide, and trivalent antimony (Sb) 3+ The chemical activity of α is significantly higher than that of pentavalent antimony (Sb). 5+ Antimony trioxide and brominated flame retardants can rapidly generate antimony bromide under thermal / electrical stress; sodium metaantimonate and antimony pentoxide are pentavalent antimony oxides, and pentavalent antimony (Sb 5+ It has low chemical activity and reacts slowly and incompletely with brominated flame retardants. Antimony bromide is the most important component for gas-phase flame retardancy, but it is easily volatilized at high temperatures and deposits as a conductive phase. High release levels of antimony bromide can significantly affect CTI (Chemical Intensity Tolerance).
[0045] Comparison of char-forming properties: Antimony trioxide promotes surface carbonization, forming a conductive path in the carbon layer and significantly reducing CTI; sodium ions in sodium metaantimonate (Na + Antimony pentoxide can also be rapidly catalyzed into carbon; antimony pentoxide has a low tendency to form carbon and limited effect of condensed phase, so it is effective in affecting CTI.
[0046] Comparison of impurity content: Antimony trioxide is directly smelted from antimony ore, resulting in high levels of residual heavy metal oxides (such as lead oxide, copper oxide, iron oxide, and arsenic trioxide). Even high-grade antimony trioxide with a purity of 99.8% contains approximately 300 ppm of lead. These heavy metals can leach out trace amounts of heavy metal ions under humid conditions, reducing surface resistivity and accelerating tracking. Sodium metaantimonate and antimony pentoxide are obtained from antimony trioxide through industrial refining. The purification process effectively removes impurities such as lead, reducing the lead content to below 50 ppm.
[0047] In summary, antimony trioxide is the most effective antimony-based synergist with bromine flame retardants. However, antimony trioxide has a strong negative impact on the tracking resistance of polymer materials, followed by sodium metaantimonate, while antimony pentoxide has the least impact. Therefore, antimony pentoxide is best suited for electrical applications in high-insulation, humid environments.
[0048] Component (D) is zinc aromatic carboxylic acid, which is a compound of an aromatic dicarboxylic acid and zinc ions.
[0049] In some embodiments, the aromatic dicarboxylic acid is selected from the group consisting of: terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, isophthalic acid, and terephthalic acid, preferably terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid, and more preferably terephthalic acid, as detailed below:
[0050]
[0051] In some embodiments, the zinc source of the aromatic zinc carboxylate is selected from one or more of zinc carbonate, basic zinc carbonate, and zinc nitrate, preferably zinc nitrate.
[0052] In some embodiments, the aromatic zinc carboxylate is synthesized using a hydrothermal method, the method comprising:
[0053] (1) Using distilled water as a medium, aromatic dicarboxylic acid and zinc source were mixed at concentrations of 0.17 mol / L and 0.3 mol / L respectively to obtain an initial suspension. Then, a sodium hydroxide solution with a concentration of 0.5 mol / L was used as a precipitant to adjust the pH of the initial suspension to neutral (pH 7). The suspension was placed in a heat-collecting magnetic stirrer and stirred in a constant temperature water bath at 80℃ for 2 hours by adjusting the stirrer. Then, the pH of the suspension was adjusted to 8~9 by sodium hydroxide precipitant and stirred for another hour.
[0054] (2) Transfer the solution obtained in step (1) into a pressure-resistant reaction vessel. After nitrogen purging, heat the reaction vessel to 200°C at a rate of 2°C / min and maintain the temperature for 100 hours to carry out the reaction.
[0055] (3) Remove the water vapor from the reaction tank, then cool the reaction tank to room temperature to obtain colorless flaky crystals. Filter the crystals, wash and dry them with distilled water to obtain the final product.
[0056] Component (E) is hydroxyapatite, whose unique hexagonal crystal structure possesses excellent ion exchange and adsorption capabilities, and calcium ions (Ca) in the crystal lattice... 2+ It can undergo ion exchange with divalent heavy metals, and its surface hydroxyl functional groups (-OH) can also adsorb free halide ions (Br). - and Cl - ).
[0057] The chemical formula of the hydroxyapatite is Ca. 10 (PO4)6(OH)2, the structure is shown in formula (IV):
[0058] (IV)
[0059] The hydroxyapatite has a purity greater than 99.0% and a pH value (10% suspension) of 6-8. It is prepared by chemical precipitation, sol-gel method or hydrothermal synthesis method, with hydrothermal synthesis method being preferred.
[0060] Component (F) is a reinforcing agent selected from one or more of glass fibers, glass microspheres and mineral fillers (such as talc, mica, kaolin, calcium carbonate, calcium silicate, magnesium carbonate), with glass fibers being preferred.
[0061] Preferably, component (G) is another additive selected from one or more of toughening agents, colorants, release agents, heat stabilizers, flow improvers and crystallization promoters.
[0062] A second aspect of the present invention provides a method for preparing the high-voltage resistant brominated flame-retardant polyamide composition, comprising melt-blending the raw material components using a single-screw or twin-screw extruder.
[0063] The high-voltage resistant brominated flame-retardant polyamide composition is a melt-prepared blend, which is melt-blended using a single-screw or twin-screw extruder. The length-to-diameter ratio (L / D) of the extruder is 32 to 52, preferably 40 to 44.
[0064] The processing temperature is set to 150~300℃, and the screw speed is set to 200~500rpm.
[0065] Feeding sequence: After the extruder is heated and melted, a side feed port is set up to add component (B) bromine flame retardant and component (E) reinforcing agent. Other material components are premixed and metered in through the main feed port of the extruder.
[0066] Venting: Venting is performed at normal pressure through openings in 1-2 barrels in front of the feed port on the extruder side, and venting is performed at pressurized openings in the second-to-last barrel of the die head, with a pressure range of 30-70 cm-Hg.
[0067] The melt from the twin-screw extruder is extruded through a die, cooled in a water tank, and then cut into pellets by a pelletizer. The collected pellets are dried to a moisture content of less than 0.1% before being packaged.
[0068] Compared with the prior art, the present invention proposes a high-voltage resistant brominated flame-retardant polyamide composition with a relative tracking index (CTI) greater than 400V and an inclination tracking index (IPT) greater than 1kV, while also possessing high flame retardancy and cost-effectiveness. The beneficial effects are reflected in at least the following points:
[0069] I. During the polymerization stage, the terminal amino groups of aliphatic polyamides are capped with acetic acid to reduce their activity, thereby improving the flame retardant and tracking resistance properties of the composition. Carboxylic acid capping of the terminal amino groups of general-purpose aliphatic polyamides (PA6 and PA66) is a low-cost, simple process that effectively improves tracking resistance without affecting mechanical properties.
[0070] Second, anionic brominated polystyrene and antimony pentoxide are preferred as the flame retardant system. Anionic brominated polystyrene has excellent temperature resistance and does not easily release hydrogen bromide during melt processing. In addition, antimony pentoxide has low binding activity with hydrogen bromide and does not easily form carbon. This combination is more suitable for electrical applications in high-insulation and humid environments.
[0071] Third, hydroxyapatite is used as an electrochemical staining modifier. Its special hexagonal crystal structure has excellent ion exchange and adsorption capabilities. Calcium ions in the lattice can exchange ions with divalent heavy metals, and the hydroxyl functional groups on the surface can adsorb free halide ions.
[0072] IV. In the composition of this invention, the aromatic zinc carboxylate combines the functions of synergistic flame retardancy and polymer stabilization, while zinc compounds provide thermal stability to polyamides. Through research and experimentation, the inventors of this invention have discovered that aromatic zinc carboxylate also exhibits excellent flame retardant effects in brominated flame-retardant polyamides. For example, zinc terephthalate degrades at approximately 400°C in an oxygen atmosphere, with the main products being carbon dioxide, carboxylic acid, and zinc oxide. Zinc oxide is a commonly used synergist in polyamide flame-retardant systems, carbon dioxide dilutes oxygen, and carboxylic acid catalyzes carbonization on the polymer surface to isolate oxygen; all of these products have flame-suppressing effects. More importantly, aromatic zinc carboxylate exhibits high stability under temperature, humidity, and discharge conditions and does not release carboxylic acid, thus having no negative impact on electrical tracking performance. Detailed Implementation
[0073] To more fully understand and demonstrate the technical solutions, objectives, and advantages of the present invention, the technical effects produced by the present invention will be further described in detail and completely below with reference to specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. It should be noted that other embodiments obtained by those skilled in the art without departing from the concept of the present invention are all within the protection scope of the present invention.
[0074] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.
[0075] The following commercially available materials were used in the examples and comparative examples:
[0076] PA66-1: Polyamide 66 purchased from Yangnong Company, with an amino-terminated content of approximately 25 mEq / kg.
[0077] PA66-2: Polyamide 66 purchased from Yangnong Company, with an amino-terminated content of approximately 55 mEq / kg.
[0078] PA66-3: Polyamide 66 purchased from Yangnong Company, with an amino-terminated content of approximately 85 mEq / kg.
[0079] PA6: Polyamide 6, trade name LX275, purchased from Luxi Chemical Company, with an amino-terminated content of approximately 45 mEq / kg.
[0080] PA610: Purchased from Huafeng Company, polyamide 610, trade name LC1624.
[0081] PA612: Purchased from Huafeng Company as polyamide 612, trade name LC1825.
[0082] PA46: Polyamide 46 purchased from Enhuali Company.
[0083] PA56: Purchased from Cathay Corporation, polyamide 56, trade name E-2260.
[0084] PA1010: Polyamide 1010 purchased from Guangyin Company.
[0085] PA11: Purchased from Arkema, polyamide 11, trade name RILSANBMNO.
[0086] PA12: Purchased from Wanhua Company as polyamide 12, trade name Wanamid L2000.
[0087] MIX-PA: refers to a mixture obtained by mixing PA610:PA612:PA46:PA56:PA1010:PA11:PA12 in a ratio of 1:1:1:1:1:1:1.
[0088] DBDPE: Decabromodiphenyl ethane purchased from Bailey Company.
[0089] BEO: Brominated epoxy resin purchased from Xingsheng Company, trade name EP-25K.
[0090] BPS-1: Purchased from Albemarle, an anionic brominated polystyrene, trade name HP-5010.
[0091] BPS-2: Purchased from Mett Company, a free radical type of brominated polystyrene, trade name XZ-6700.
[0092] MIX-FR refers to a mixture obtained by mixing DBDPE, BEO, BPS-1, and BPS-2 in a ratio of 1:1:1:1 by Jinlun Company.
[0093] Sb2O3: Antimony trioxide purchased from Flashstar Corporation.
[0094] Sb2O5: Antimony pentoxide purchased from Flashstar Corporation.
[0095] NaSbO3: Purchased from Anter Company, which manufactures sodium antimonate.
[0096] HAP: Hydroxyapatite purchased from Budenheim Company, trade name BUDITT31.
[0097] GF: Glass fiber purchased from Shandong Fiberglass Company, trade name 995-10P, with a single filament diameter of 10μm.
[0098] GB: Glass microspheres purchased from 3M, trade name IM16K.
[0099] TD: Magnesium silicate purchased from Imfabi, trade name HTPultra5L.
[0100] Clay: Purchased from Carmin Company's washed ultrafine kaolin.
[0101] MIX-FILLER: refers to a mixture obtained by mixing GF:GB:TD:Clay in a ratio of 1:1:1:1 by Jinlun Company.
[0102] CBK: Purchased 50% concentration carbon black masterbatch from Cabot Corporation, trade name UN2014.
[0103] Preparation of component (D) zinc aromatic carboxylate for use in the examples and comparative examples:
[0104] Step 1: Using distilled water as a medium, terephthalic acid and zinc nitrate were mixed at concentrations of 0.17 mol / L and 0.3 mol / L respectively to obtain an initial suspension. Then, a 0.5 mol / L sodium hydroxide solution was used as a precipitant to adjust the pH of the initial suspension to neutral (pH 7). The suspension was placed in a heat-collecting magnetic stirrer and stirred in a constant temperature water bath at 80℃ for 2 hours by adjusting the stirrer. Then, the pH of the suspension was adjusted to 8-9 with sodium hydroxide precipitant and stirring was continued for 1 hour.
[0105] Step 2: Transfer the solution obtained in Step 1 into a pressure-resistant reaction vessel. After nitrogen purging, heat the reaction vessel to 200°C at a rate of 2°C / min and maintain the temperature for 100 hours to carry out the reaction.
[0106] Step 3: Remove the water vapor from the reaction tank, then cool the reaction tank to room temperature to obtain colorless flaky crystals. Filter the crystals, wash and dry them with distilled water to obtain zinc terephthalate (Zn-PTA).
[0107] Following the methods described in steps one through three above, the following zinc compounds were prepared: zinc isophthalate, zinc 1,4-naphthalenedicarboxylate, zinc 1,5-naphthalenedicarboxylate, zinc 2,6-naphthalenedicarboxylate, zinc 2,7-naphthalenedicarboxylate, zinc isophthalic acid, and zinc terephthalic acid.
[0108] MIX-Zn refers to a mixture obtained by mixing zinc isophthalate, zinc 1,4-naphthodicarboxylate, zinc 1,5-naphthodicarboxylate, zinc 2,6-naphthodicarboxylate, zinc 2,7-naphthodicarboxylate, zinc isophthalic acid, and zinc terephthalic acid in a ratio of 1:1:1:1:1:1:1, obtained by Jinlun Company. The zinc content of the mixture is approximately 29.0%.
[0109] Preparation method
[0110] As shown in Table 1, weigh each component and then add it to a twin-screw extruder for melt processing.
[0111] Extruder screw nominal diameter: 35mm;
[0112] Extruder screw length-to-diameter ratio: 40;
[0113] Processing temperature range: 150~300℃;
[0114] Main unit speed range: 300 rpm;
[0115] Feeding sequence: After the extruder is heated and melted, a side feed port is set up to add component (B) bromine flame retardant and component (E) reinforcing agent. Other material components are premixed and metered in through the main feed port of the extruder.
[0116] Venting: Venting is performed at normal pressure through openings in 1-2 barrels in front of the feed port on the extruder side, and venting is performed at pressurized openings in the second-to-last barrel of the die head, with a pressure range of 30-70 cm-Hg.
[0117] The melt from the twin-screw extruder is extruded through a die, cooled in a water tank, and then cut into pellets by a pelletizer. The collected pellets are dried to a moisture content of less than 0.1% before being packaged.
[0118] Vertical burning performance was tested according to the method specified in UL94, with a test specimen size of 125mm × 13.0mm × 0.4mm.
[0119] The relative tracking index (CTI) was measured according to the method specified in IEC 60112, with a test piece size of 60mm × 60mm × 3mm.
[0120] Examples and Comparative Examples
[0121] Tables 1 and 2 list the performance test results of the compositions in each embodiment.
[0122] Table 1
[0123]
[0124] Table 2
[0125]
[0126] Comparative Examples 1, 2, and 3 verified the effect of different terminal amino group content levels of PA66 on the flame retardant and tracking resistance properties of the polyamide compositions. It was found that the higher the terminal amino group content of PA66, the worse the flame retardant properties of the composition. When the terminal amino group content of PA66 reached 85 mEq / kg, the burning time of the composition was significantly prolonged, and dripping ignited defatted cotton. Comparative Examples 1-3 all used antimony trioxide for synergistic flame retardancy; the compositions exhibited strong charring effects, and the CTI test results were all 250V, with no differences observed.
[0127] Comparative Examples 1 and 4 were used to verify the effects of anionic and free radical brominated polystyrene on the flame retardant and tracking resistance properties of the polyamide composition. Comparative Example 4, which used anionic brominated polystyrene, showed better flame retardant effect on the polyamide, and its CTI value was 25V higher than that of Comparative Example 3, which used free radical brominated polystyrene for flame retardancy.
[0128] Comparative Examples 4 and 5 were used to verify the effects of antimony trioxide and antimony pentoxide on the flame retardant and tracking resistance properties of the polyamide composition. Comparative Example 4, which used antimony trioxide, showed better flame retardant properties, while the composition using antimony pentoxide showed better tracking resistance and a higher CTI value.
[0129] Comparative Examples 5, 1, and 2 were used to verify the effects of antimony pentoxide and sodium metaantimonate on the flame retardant and tracking resistance properties of the polyamide composition. The comparison revealed that while antimony pentoxide had weaker flame retardancy, its tracking resistance was superior to that of sodium metaantimonate. The addition of zinc terephthalate mitigated the weaker flame retardancy of antimony pentoxide.
[0130] Examples 1, 3, 7, and 8 verified the effect of different hydroxyapatite ratios on the tracking resistance of polyamide compositions. Compared with 0.5% HAP, the CTI of the composition increased from 325V to 375V when 5% HAP was added. However, no further increase in CTI value was observed when the HAP ratio was increased to 7% and 10%, and no negative impact of HAP on flame retardant properties was observed.
[0131] Comparing Comparative Examples 4 and 6, it was found that carbon black significantly degrades the CTI value of the brominated flame-retardant polyamide composition, while hydroxyapatite significantly improves the electrical tracking resistance even in compositions with added carbon black, achieving a CTI value close to that of the natural material.
[0132] Examples 5, 6, and 7 validate the optimized high-voltage resistant brominated flame-retardant polyamide composition. By using zinc terephthalate and bromine / antimony compound to improve flame-retardant stability, the addition ratio of bromine / antimony flame retardant can be reduced, which achieves the goal of improving the composition's resistance to electrical tracking while also reducing formulation costs.
[0133] Example 8 demonstrates that zinc aromatic carboxylate and hydroxyapatite also improve the electrical tracking performance of formulations for other aliphatic polyamides and brominated flame retardants.
[0134] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A high-voltage resistant brominated flame-retardant polyamide composition, characterized in that, It includes the following components, expressed as a percentage by mass: (A) Aliphatic polyamide 30~80 wt% (B) Bromine-based flame retardant 10~30 wt% (C) Antimony-based synergist 0.5~10 wt%; (D) Aromatic carboxylic acid zinc 0.5~10 wt% (E) Hydroxyapatite 0.5~5 wt% (F) Reinforcing agent 0.1~50 wt%; (G) Other adjuvants 0~5 wt%; The sum of the mass percentages of components (A) to (G) is 100 wt%.
2. The high-voltage resistant brominated flame-retardant polyamide composition according to claim 1, characterized in that, The aliphatic polyamide is a semi-crystalline polymer with a melting temperature of 150~300℃. It is selected from one or more of PA-XY obtained by polycondensation reaction of aliphatic dicarboxylic acid and aliphatic diamine having not less than four carbon atoms, and PA-Z obtained by ring-opening polymerization of lactam, wherein X is the number of carbon atoms of the diamine, Y is the number of carbon atoms of the dicarboxylic acid, and Z is the number of carbon atoms of the lactam. The aliphatic dicarboxylic acid is selected from the group consisting of: oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, heptaic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, octadecanoic acid, and eicosanoic acid. The aliphatic diamine having not less than four carbon atoms is selected from the group consisting of: butanediamine, pentapentanediamine, ethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecylethylenediamine, dodecamethylenediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine; The lactam is selected from the group consisting of butyrolactam, ε-caprolactam, heptanolactam, undecanolactam and dodecanolactam.
3. The high-voltage resistant brominated flame-retardant polyamide composition according to claim 2, characterized in that, Both the PA-XY type polyamide and the PA-Z type polyamide have 10~60 mEq / kg terminal amino groups at the end of their molecular chains; The structure of the PA-XY type polyamide is shown in Formula I: (I) In formula (I), A1 represents H+ or CH3-CO-, and B1 represents -OH; The structure of the PA-Z type polyamide is shown in Formula II: (II) In formula (II), A1 represents H+ or CH3-CO-, and B1 represents -OH.
4. The high-voltage resistant brominated flame-retardant polyamide composition according to any one of claims 1 to 3, characterized in that, The aliphatic polyamide is selected from one or more of PA6, PA11, PA12, PA46, PA56, PA66, PA610, PA612 and PA1010.
5. The high-voltage resistant brominated flame-retardant polyamide composition according to claim 1, characterized in that, The brominated flame retardant is selected from one or more of decabromodiphenyl ethane, brominated epoxy resin, and brominated polystyrene.
6. The high-voltage resistant brominated flame-retardant polyamide composition according to claim 1, characterized in that, The antimony-based synergist is selected from one or more of antimony trioxide, sodium metaantimonate, and antimony pentoxide.
7. The high-voltage resistant brominated flame-retardant polyamide composition according to claim 1, characterized in that, The aromatic zinc carboxylic acid is a compound of an aromatic dicarboxylic acid and a zinc ion; wherein: The aromatic dicarboxylic acid is selected from the group consisting of: terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, isophthalic acid, and terephthalic acid. The zinc source for the zinc ions is selected from one or more of zinc carbonate, basic zinc carbonate, and zinc nitrate.
8. The high-voltage resistant brominated flame-retardant polyamide composition according to claim 1, characterized in that, The chemical formula of the hydroxyapatite is Ca. 10 (PO4)6(OH)2, the structure is shown in formula (IV): (IV) The hydroxyapatite is prepared by chemical precipitation, sol-gel method or hydrothermal synthesis, with a purity greater than 99.0%, and simultaneously meets the requirement that the pH value of a 10% hydroxyapatite suspension is 6-8.
9. The high-voltage resistant brominated flame-retardant polyamide composition according to claim 1, characterized in that, The reinforcing agent is selected from one or more of glass fiber, glass microspheres, talc, mica, kaolin, calcium carbonate, calcium silicate, and magnesium carbonate; And / or the other additives are selected from one or more of toughening agents, colorants, release agents, heat stabilizers, flow improvers and crystallization promoters.
10. A method for preparing the high-voltage resistant brominated flame-retardant polyamide composition according to any one of claims 1 to 9, characterized in that, include: The raw material components are produced by melt blending using a single-screw or twin-screw extruder, wherein the length-to-diameter ratio (L / D) of the single-screw or twin-screw extruder is 32-52; the processing temperature is 150-300 ℃; and the screw speed is 200-500 rpm.
Citation Information
Patent Citations
Flame-retardant polyamide material and preparation method thereof
CN104693792A
Flame-retardant reinforced polyamide composition and preparation method thereof
CN112759927A
Method for improving tracking resistance of thermoplastic resin
CN113574104A
Flame-retardant nylon composition as well as preparation method and application thereof
CN114196199A
Electrical and electronic articles comprising polyamide compositions
CN115516006A
Cited By
A bromine flame retardant compound composition with high CTI value and its preparation method and application
CN122427459A